The Role of Local Benefits in Global Environmental Programs - Global Environment Facility (Washington, DC: Global Environment Facility, 2012)
This study analyzes the interrelationship between local benefits and global environment benefits in the Global Environment Facility (GEF) strategies and projects in order to: Enhance GEF policies, strategies, and project design and implementation so these can effectively promote the potential for local gains in those global environmental programs where actors need to be mobilized for long-term support of sound environmental management, costs incurred by local communities for supplying global environmental goods need to be reduced, and possible negative impacts need to be ameliorated. Strengthen GEF monitoring and evaluation policies and processes to develop indicators for, and enhance the tracking of, local benefits and negative impacts. Expand the body of existing operational knowledge of good practices and experiences germane to pursuing global environmental issues and of constraints or fallacies to be avoided in operations. Disseminate widely the most valuable lessons of existing experience and show how these lessons can be implemented in future GEF operations.